(untitled) (Herald of Journalism, 2016)
This article discusses the impact of global climate change on Kazakh- stan using examples of the recent flood disaster and other ecological crises in Almaty and its oblast against the background of the media’s role in pre- venting environmental disasters. The article argues that media have to play a watchdog role on environmental issues and have to inform citizens of how environmental issues can affect their lives. It cites relevant examples from the fire and flood damage in Los Angeles and surrounding areas and shows how future environmental disasters can affect the Almaty region’s tourism industry.